PERSPEKTIF EKONOMI ISLAM TERHADAP FAKTOR PENDUKUNG EKSISTENSI PASAR TRADISIONAL PANORAMA KOTA BENGKULU - Ajis, Pajri Abdul; Idwal; Padlim Hanif (Universitas Muhammadiyah Bengkulu, 2025)
The objective of this research is to understand the supporting factors for the existence of Panorama Market and the Islamic Economic perspective on these factors concerning the existence of Panorama Market in Bengkulu City. This type of research is field research using a qualitative descriptive method. The data collection techniques employed are observation, interviews, and documentation. The results of the research can be summarized as follows: (1) Panorama Traditional Market has several supporting factors for its current existence. These factors include having lower prices, offering a variety of products, and having a strategic location. With these factors, Panorama Traditional Market has successfully maintained its presence among the community. (2) Panorama Market has implemented Islamic economic principles, as there is no dishonesty, particularly in transactions. All three factors supporting the existence of Panorama Market adhere to Islamic economic principles.